BALANÇO EMERGÉTICO EM AGROSSISTEMAS DE PRODUÇÃO FAMILIAR - Eurich, Joelcio (2011)
Even with the prominence of the current discussions about sustainable models of development, studies and adoption of techniques of sustainable rural development are not common. The generation of technology as well as the measuring the real sustainability of production systems is incipient. This study aimed the application of the emergy analysis to evaluate the agroecosystems sustainability of two family dairy farms. Two properties were studied: the Alcerich farmstead, classified as traditional, located in Palmeira – PR, and the Meier Family farmstead, that adopts the Voisin Rational Grazing System - PRV, located in the municipality of Dionisio Cerqueira - SC. In the emergy analysis we characterized the production systems, elaborated the systemic diagram, organized the emergy evaluation table and determined the traditional and modified (based on the values of partial renewability emergy indices). It was also calculated the values of economic return and socio-land elationship.Transformity values Tr = 486,087 sej J-1 and Tr = 836,011 sej J-1, respectively calculated for the Alcerich and Meier family farmsteads, show that the former has a higher emergy efficiency, but this result is based on the higher use of no renewable resources.The calculated sustainability index for the Alcerich farm, based on the classical methodology (SI = 1.77), and modified methodology (SI = 2.13), confers a classification as sustainable at medium-term and high demand from resources of the economy.To the Meier farm the SI values = 3.15 and 5.94, for the modified and classical methods, confers a classification as sustainable at medium-term and sustainable at long term, respectively, based on consistent use of energy.The values of economic returns of 49 and 61, and the socio-land relationship indicators, from 16.00 to 6.25 po ha-1 for the Alcerich and Meier farms, respectively, emphasize the socioeconomic importance of the properties.The emergy methodology provided a broad view of the potential and bottlenecks of the systems sustainability. The Meier Family farm, based on the PRV system, showed a greater sustainability regarding a holistic understanding of the concept.